Getting it, having it, keeping it up : straight men's sexuality in public and private - Montemurro, Beth, 1972- (Rutgers University Press, 2022)
"When straight men talk to each other about their sex lives, they often boast about sexual exploits and brag about the hot women they have slept with. Yet this competitive bluster covers up deep-seated anxieties about measuring up to impossibly virile cultural ideals of masculinity. So how do straight men really feel about sex, women, and manhood-and how do those feelings clash with their public performance of manliness? This landmark sociological study emerges from in-depth interviews with nearly one hundred straight American men aged 20 to 68 from a variety of socioeconomic and ethnic backgrounds. Getting It, Having It, Keeping It Up examines how these men use sex with women as a way of affirming their manhood-and how they view themselves as failures when they are unable to "score." It also explores the effects of aging and erectile dysfunction on the men's self-image. However, the life stories collected here are not just about performance anxiety, as this research reveals ways that some straight men have resisted masculine cultural scripts to form mutually nurturing relationships with women. Addressing everything from pornography to marriage, this book shares straight men's most intimate experiences of failure, triumph, heartbreak, and love"--